2021
DOI: 10.1016/j.cjca.2021.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Longitudinal Strain Predicts Survival in Patients With Functional Tricuspid Regurgitation

Abstract: See editorial by Hassanin et al., pages 945e948 of this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Numerous studies have shown that reduced RVF is associated with worse prognosis in severe TR [ 15 , 16 ]. However, it still remains unclear if the same lower limits of normality apply for each of the parameters as in patients without TR.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that reduced RVF is associated with worse prognosis in severe TR [ 15 , 16 ]. However, it still remains unclear if the same lower limits of normality apply for each of the parameters as in patients without TR.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study from Germany reported that mortality in patients with TR increased with increasing of TR level, but they also found that reduced TAPSE (<18.5 mm), decreased FAC (<35%), and impaired free-wall RV longitudinal strain (>-18%) were predictors of mortality in the observed population of 1089 patients with TR [35]. However, reduced free-wall RV longitudinal strain was superior predictor of mortality in comparison with reduced FAC (<35%) and TAPSE in the whole population [36]. Ancona et al involved only patients with severe TR who were mostly presented with symptoms of RV heart failure and advanced NYHA class [6].…”
Section: Right Ventricular Remodeling and Its Predictive Importance In Ftrmentioning
confidence: 92%
“…67,68 Right ventricular function is an important stage-defining feature of almost all patients with VHD; it strongly affects survival and the risk of intervention. 69 Reduced right ventricular free wall longitudinal strain (see Fig. 2) may be a red flag for postoperative right ventricular afterload mismatch 70 and worse outcomes in patients with apparently normal preoperative fractional area change and tricuspid anulus excursion.…”
Section: Heart Valve Diseasesmentioning
confidence: 99%
“…Right ventricular function is an important stage-defining feature of almost all patients with VHD; it strongly affects survival and the risk of intervention 69 . Reduced right ventricular free wall longitudinal strain (see Fig.…”
Section: Heart Valve Diseasesmentioning
confidence: 99%